2011
DOI: 10.1007/s00894-011-1239-5
|View full text |Cite
|
Sign up to set email alerts
|

How to simulate affinities for host–guest systems lacking binding mode information: application to the liquid chromatographic separation of hexabromocyclododecane stereoisomers

Abstract: A novel approach for the simulation of host-guest systems by systematically scanning the host molecule's orientations within the guest cavity is presented along with a thermodynamic strategy for determining preferential binding modes and corresponding optimal interaction energies between host and guest molecules. By way of example, the elution order of hexabromocyclododecane stereoisomers from high performance liquid chromatography separation on a permethylated β-cyclcodextrin stationary phase has been compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Charges were assigned with the am1bcc method , approximating restrained electrostatic potential (RESP) charges . As described previously, 60 initial orientations were generated of each ligand’s global minimum conformation sharing the same geometric center which was superimposed with the geometric center of the crystallized E 2 molecule at the binding site. Explicit water solvation was included using Amber’s ffamber_tip3p model which is part of the GAFF–Gromacs MD interface denoted as amber ports .…”
Section: Methodsmentioning
confidence: 99%
“…Charges were assigned with the am1bcc method , approximating restrained electrostatic potential (RESP) charges . As described previously, 60 initial orientations were generated of each ligand’s global minimum conformation sharing the same geometric center which was superimposed with the geometric center of the crystallized E 2 molecule at the binding site. Explicit water solvation was included using Amber’s ffamber_tip3p model which is part of the GAFF–Gromacs MD interface denoted as amber ports .…”
Section: Methodsmentioning
confidence: 99%
“…3), followed by the γ-enantiomers with (+) γ-eluting ahead of (−) γ -HBCD (Janák et al, 2005). In order to explain this order of elution, (Durmaz et al, 2012), hypothesized that interaction of HBCD enantiomers with β-permethylated cyclodextrin is more likely in water, while enantiomers elution rate is higher in more hydrophobic solvents (i.e. acetonitrile, etc).…”
Section: Composition Of Chiral Stationary Phasementioning
confidence: 98%
“…acetonitrile, etc). Using a multi-mode Hamiltonian dynamics simulation model, (Durmaz et al, 2012) calculated the interaction energies of HBCD enantiomers with β-permethylated cyclodextrin and they found that the experimental capacity factors k of enantiomers determined by HPLC are increasing with the absolute value of mean interaction energies of the enantiomers (data taken from (Durmaz et al, 2012) were plotted in Fig. 3).…”
Section: Composition Of Chiral Stationary Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, all geometries were minimized with the conjugate gradient method [13,14] and the lowest energy geometry was chosen as an estimate for the global minimum conformation. As described in Durmaz et al [15], this strategy seems to provide realistic global minima conformations for small molecules. This conformer was then parameterized according to the general Amber force field [16] (GAFF) using Antechamber from the AmberTools v1.4 package [17].…”
Section: Quantum Chemical and Classical Simulation Of Ergopeptidesmentioning
confidence: 98%